Bicyclol protects HepG2 cells against D-galactosamine- induced apoptosis through inducing heat shock protein 27 and mitochondria associated pathway - Bao Xiu-qi; Liu Geng-tao (Acta Pharmacologica Sinica, 2016)
Aim: To study the inducing effect of bicyclol on heat shock protein 27 (HSP27) and its role on anti-apoptosis in HepG2 cells intoxicated with D-galactosamine (D-GaIN). Methods: HepG2 cells were treated with various concentrations of bicyclol and then subjected to D-GaIN intoxication. Apoptosis was assayed by hoechst 33258 staining and flow cytometry analysis. HSP27, cytochrome c, apoptosis inducing factor (AIF) and c-Jun N-terminal kinase (JNK) were assayed by Western blot. Heat shock factor 1 (HSF1) was determined by electrophoretic mobility shift assay and the interactions of HSP27 with cytochrome c and AIF were detected by co-immunoprecipitation. Results: The results showed that bicyclol induced HSP27 protein and mRNA expression in HepG2 cells in both time- and dose-dependent manners (the maximal response: 1.23 fold increase at 100 μmol/L). Bicyclol treatment stimulated HSF1 activation and increased the HSF1-HSE binding activity (the maximal response: 2.1 fold increase at 100 μmol/L). This inducing effect of bicyclol on HSP27 and HSF1 was markedly blocked by quercetin. Pretreatment of the cells with bicyclol markedly attenuated D-GaIN-induced apoptosis and the release of cytochrome c and AIF from mitochondria. The induced HSP27 by bicyclol suppressed the activity of caspase-3 and the phosphorylation of JNK caused by D-GaIN in HepG2 cells. All the above effect of bicyclol against D-GaIN-induced hepatocytes apoptosis were significantly reversed by quercetin. Conclusion: HSP27 is involved in the anti-hepatocytes apoptosis of bicyclol, and this effect of bicyclol-induced HSP27 is mainly through inhibition of mitochondria and JNK apoptotic pathways.